Factors affecting Consumer Purchase Intention for Dairy Products in Kathmandu - Nath, Rupak; Chaulagain, Tilak Raj (Nepalese Journal of Agricultural Sciences, 2025)
The research delved into the intricate factors affecting consumer choices when it came to purchasing dairy products in Kathmandu, Nepal. It examined various psychological factors like attitudes, product knowledge, health consciousness, brand image, and taste preferences, along with external influences such as social networks, price perception, and product accessibility. Additionally, it analyzed demographic variables like age, gender, income, and education to understand their impact on consumer intentions. Using a mixed-methods approach, the study utilized structured questionnaires to survey 385 respondents, employing descriptive statistics and analytical tools like Chi-square, one-way ANOVA, and linear regression to construct a theoretical model. The findings highlighted the significant role of consumer attitudes, with positive outlooks correlating strongly with purchase intentions. Health consciousness and taste preferences also emerged as key drivers, underlining the importance of promoting health benefits and product taste in marketing strategies. A regression equation revealed the nuanced relationships among these factors, with health consciousness, social networks, price perception, and product accessibility standing out as significant influencers. The study emphasized the importance of brand image, social networks, and external factors alongside demographic variables in shaping consumer behavior. These insights offered valuable guidance to dairy product marketers and policymakers, suggesting strategies like improving consumer product knowledge, building strong brand images, and leveraging social networks. Additionally, recommendations included implementing competitive pricing, targeted marketing, ongoing research, and ethical considerations to adapt to changing consumer preferences effectively.